2016
DOI: 10.1109/tmtt.2016.2586479
|View full text |Cite
|
Sign up to set email alerts
|

Chirping Techniques to Maximize the Power-Handling Capability of Harmonic Waveguide Low-Pass Filters

Abstract: A novel chirping technique is applied to the design of very high-power waveguide harmonic low-pass filters. The technique could be used, for instance, to avoid multipactor testing in multicarrier systems such as the output multiplexer of a communications satellite. The novel chirped filter shows low insertion loss, all-higher order mode suppression, and broad stopband rejection up to the third harmonic. The paper focuses on the maximization of the filter power-handling capability without affecting its excellen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The same method could be applied to porous Si-SiO 2 structures in the UV range. Notably, one way to obtain a broader optical response from these kinds of photonic structures is using chirping techniques 52 .…”
Section: Discussionmentioning
confidence: 99%
“…The same method could be applied to porous Si-SiO 2 structures in the UV range. Notably, one way to obtain a broader optical response from these kinds of photonic structures is using chirping techniques 52 .…”
Section: Discussionmentioning
confidence: 99%
“…4, to ease the fabrication by CNC milling [26] - [29]. In fact, from the thorough analysis performed in [30], it can be concluded that, considering appropriate geometries of the bandstop step-shaped elements, it is possible to fabricate (by CNC milling) low-pass filters addressing a wide stop band and featuring in practice (almost) unlimited power handling constraints (and, consequently, no need for costly high-power testing!). As an example, a device designed for Ka-band multibeam satellite payloads is shown in Fig.…”
Section: Low-pass Filter Designmentioning
confidence: 99%
“…with Meandered Topology Although compact high-power LPFs have been obtained in [21]- [23] an E-plane bend cannot be embedded in these types of filters. Hence, if an E-plane bend is required before or after the LPF, two different structures will be needed (with their corresponding flanges, screws, etc.).…”
Section: Rectangular Waveguide Filtersmentioning
confidence: 99%